Clinical and microbiological evaluation of epidural and regional anaesthesia catheters in injured UK military personnel. Issue 4 (15th June 2015) - Wood, Paul; Gill, M; Edwards, D; Clifton, P; Bullock, C; Aldington, D
Abstract : Introduction: The adoption of regional and epidural analgesia in UK military personnel injured in action during Op HERRICK increased from 2008, in line with structural and environmental developments in the UK medical treatment facility. Historically, there have been concerns that invasive analgesic techniques could carry an increased risk of infection, due to the mechanism of injury and the environmental conditions in which the injuries were sustained. Consequently, the epidural and continuous peripheral nerve blockade (CPNB) catheters that were inserted in UK military personnel during a 33-month period of Op HERRICK were clinically and microbiologically examined, after subsequent admission to the University Hospitals Birmingham (UHB) NHS Trust. Methods: Data on epidural and CPNB insertions were collected via the specialist pain service at UHB over the study period, including de novo and replacement insertions performed in both Afghanistan and the UK. Patients were regularly reviewed and relevant clinical concerns were documented in patients' case notes as necessary. The anatomical site, duration of placement and the results of microbiological culture of the epidural and CPNB catheter tips were all recorded. Results: Overall, 236 catheters were assessed, of which 151 catheter tips (64%) were cultured (85 epidural, 66 CPNB). Of these, 48 grew bacteria (34% of cultured epidurals and 29% of cultured CPNB). There was no difference between the colonisation rates of epidurals inserted in Afghanistan and the UK. Only one infection related to a misplaced epidural catheter was confirmed. Conclusions: With the exception of the epidural (34%) and proximal sciatic (42%) catheters, these figures, in a military cohort characterised by significant injury scores, are consistent with those reported for civilian surgical patients. The results strongly support the expansion of regional analgesia during Op HERRICK from 2008 onwards. The outcomes suggest a possible translation into civilian major trauma practice.